European oil price uncertainty: a panel data approach / Natrah Che Ibrahim, Tismazammi Mustaffa and Nur Idalisa Norddin - Che Ibrahim, Natrah; Mustaffa, Tismazammi; Norddin, Nur Idalisa (2017)
This paper investigates the significant macroeconomic determinant such as inflation, exchange rate, oil export and oil import affecting oil price in 10 European countries namely Austria, Denmark, France, Germany, Greece, Italy, Norway, Turkey, United Kingdom and Spain from 1994 to 2014. Panel data are be use to run this analysis regarding the relationship between the dependent and independent variable. By employing Fixed Effect Estimation Model, the empirical result revealed that the oil price is influenced by the selected macro-economic factor. In particular, the evidence shows that inflation and oil import are significantly affect oil price in the majority of this country. Oil export and exchange rate does not give impact to oil price which mean insignificantly relationship between oil prices.